Expired Pharmaceutical Drugs as Tribopositive Material for Triboelectric Nanogenerator. (17th October 2021) - Chougale, Mahesh Y.; Saqib, Qazi Muhammad; Khan, Muhammad Umair; Shaukat, Rayyan Ali; Kim, Jungmin; Dubal, Deepak; Bae, Jinho
Abstract: The disposal of expired pharmaceutical drugs is largely unattended, which leads to massive environmental pollution. Herein, a novel strategy is demonstrated to turn expired drugs into a novel tribopositive material in a triboelectric nanogenerator (TENG). To realize the proposed method, three types of expired tablets such as paracetamol, nimesulide, and guaiphenesin are employed as tribopositive materials in TENG devices. Owing to their high electron donating capability with hydroxyl and carbonyl functional groups, these drugs reveal strong positive triboelectric potential. The proposed TENG devices yield open circuit voltages ranging from 267 to 561 V, while the short circuit current varies from 28 to 53 µA under a pneumatic air cylinder of 10 Hz. Impressively, the drug‐based TENG can scavenge energy to light up to 169 commercial light‐emitting diodes (LEDs). This excellent performance makes these expired drugs a promising positive tribomaterial, providing a possible solution to recycle a huge amount of pharmaceutical waste. These materials and reuse strategies are expected to aid the development of alternative sustainable energy conversion technology. Abstract : In order to reduce pharmaceutical waste pollution and resolve energy resource problems, this work demonstrates a unique strategy for reutilization of expired pharmaceutical drugs in triboelectric nanogenerator (TENG) applications. The present investigation provides a sustainable solution for a clean environment with efficient energy scavenging from recycling of pharmaceutical waste.